(untitled) (Research, Society and Development, 2020)
The processing of fruits produces a high amount of waste, which can result in being a form of environmental pollution, and may cause health risks. However, fruit wastes are sources of high nutritional level compounds, which can be used to prepare nutritious food products, the source of low-cost nutrients. Given the above, the present work aimed to produce a shake beverage from tropical fruit wastes, limiting the environmental impact and adding nutritional value to the waste. The fruit wastes used were: orange, lemon, guava, banana, mango, acerola, passion fruit and tangerine. Six shake formulations were prepared by varying the wastes used in each. Chemical and physicochemical analyses of the wastes and the shakes were carried out. In addition, microbiological analyses and sensorial acceptance tests were performed on the shake. The shake had good amounts of ascorbic acid and low lipid content. Evaluating the results of the sensorial acceptance tests, it was noticed that the product, for the most part, was well accepted by the tasters, and the highest marks were awarded by the tasters who declared they practiced sports regularly. Thus, the different developed shake formulations have the potential to be introduced in the market.